2009
DOI: 10.1007/s00167-008-0704-x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of side-cutting implantation instruments for total knee arthroplasty

Abstract: A new generation of implantation instruments were developed for quadriceps sparing surgical approaches during total knee arthroplasty (TKA). There is little information on the accuracy of the bone cuts performed with the side-cutting technique. A total of 100 patients were randomized to undergo computer-assisted TKA or non-navigated TKA using a mini-subvastus surgical approach and side-cutting implant instrumentation. The radiographic parameters, clinical outcomes and knee scores were evaluated 3 months postop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…After applying those to selection criteria, 21 articles with clinical outcomes were included in this metaanalysis. Among these studies, 11 studies 1,4,6,18-25 with an adequate method of randomization generation and a low risk of bias were placed in Group A, and 10 studies [26][27][28][29][30][31][32][33][34][35] with a relatively high risk of bias were placed in Group B. All included trials adequately performed and reported the results of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After applying those to selection criteria, 21 articles with clinical outcomes were included in this metaanalysis. Among these studies, 11 studies 1,4,6,18-25 with an adequate method of randomization generation and a low risk of bias were placed in Group A, and 10 studies [26][27][28][29][30][31][32][33][34][35] with a relatively high risk of bias were placed in Group B. All included trials adequately performed and reported the results of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Seven studies reporting operative time were included. 1, 19,21,26,28,31,32 In total, the meta-analysis was performed on 743 patients. Of these patients, 374 patients were operated on using computer-assisted TKA and 369 patients using conventional TKA.…”
Section: Operative Timementioning
confidence: 99%
See 1 more Smart Citation
“…The mini-subvastus approach was used in 45 knees, and the mini-parapatellar approach was used in 5 knees without eversion of the patella. The MIS Quad-Sparing instrumentation (Zimmer Biomet Holdings Inc., Warsaw, IN, USA) was used when cutting the femur and tibia from the medial side [13, 14]. The posterior cruciate ligament (PCL) was sacrificed, and the patella was resurfaced in all cases.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to conventional methods, computer-assisted navigation improves orientation and alignment of the components, [12][13][14] although other studies found no significant differences between them. [15][16][17] Cementation and impaction of the components can introduce a considerable error in alignment, regardless of the accuracy of the resection planes. 18 Computer-assisted navigation improves the accuracy and reproducibility of prosthetic component orientation, 19,20 although there was no significant difference in clinical outcome or complication rates.…”
Section: Surgical Techniquementioning
confidence: 99%